BD+15 2940 AND HD 233604: TWO GIANTS WITH PLANETS CLOSE TO THE ENGULFMENT ZONE - Nowak, G.; Niedzielski, A.; Wolszczan, A.; Adamów, M.; Maciejewski, G. (The Astrophysical journal, 2013)
We report the discovery of planetary-mass companions to two red giants by the ongoing Penn State-Torun Planet Search (PTPS) conducted with the 9.2 m Hobby-Eberly Telescope. The 1.1 M sub([middot in circle]) K0-giant, BD+15 2940, has a 1.1 M sub(J) minimum mass companion orbiting the star at a 137.5 day period in a 0.54 AU orbit what makes it the closest-in planet around a giant and possible subject of engulfment as the consequence of stellar evolution. HD 233604, a 1.5 M sub([middot in circle]) K5-giant, is orbited by a 6.6 M sub(J) minimum mass planet which has a period of 192 days and a semi-major axis of only 0.75 AU making it one of the least distant planets to a giant star. The chemical composition analysis of HD 233604 reveals a relatively high super(7)Li abundance which may be a sign of its early evolutionary stage or recent engulfment of another planet in the system. We also present independent detections of planetary-mass companions to HD 209458 and HD 88133, and stellar activity-induced radial velocity variations in HD 166435, as part of the discussion of the observing and data analysis methods used in the PTPS project.